STRATEGI RENCANA PEMASARAN PERUMAHAN DALAM MENINGKATKAN PENJUALAN - Abdul Kamil, Imam; Alief Gilang, Muhamad; Pamungkas, Gilang; Abdillah, Ilham; Sundari, Asri (Pelita Nusa Jurnal, published by the Institute for Research and Community Service (LP2M) of the Pelita Nusa Islamic Religious College West Bandung (STAI PENUS), 2025)
This research aims to find problems, solve problems and develop new knowledge, by analyzing a case to find out a marketing plan that is suitable for marketing in